A comparative study between ultrasound-guided ilioingunial/iliohypogastric nerve block versus transverse abdominis plane block in patients undergoing oblique inguinal hernia repair - Ahmed Fathi Elwany; Sohair Abass Mohamed; Amr Mohamed Abd EL-Fatah; Nasser El-sayed El-sayed; Ghada Mohamed Samir (Ain Shams Journal of Anesthesiology, 2022)
Abstract Background Combined ilioinguinal-iliohypogastric (IIN/IHN) block and transverse abdominis plane (TAP) block are used under ultrasound (USG) visualization for postoperative pain control in patients undergoing inguinal hernia repair surgery. This study compares USG-guided TAP versus IIN/IHN block for post-operative analgesia efficacy in adults undergoing inguinal hernia surgery, among 100 patients randomized into group A received TAP block by using levobupivacaine 0.5% 25 ml and group B received IIN+IHN blocks by using levobupivacaine 0.5% 10 ml before induction of general anesthesia. Results The mean duration (in minutes) to require rescue analgesia was found to be 1003.2 ± 99.6 (min) in group A and 1317 ± 69 (min) in group B. In a comparison of these two values the difference in the meantime to rescue analgesic requirement was statistically significant (p < 0.001). Conclusions USG-guided IIN/IHN block delays the need for rescue analgesia and reduces the postoperative analgesic requirement compared to USG-guided TAP block.